Productivity of Sondong Fishing Gear in Selat Akar Village of Kepulauan Meranti Regency - Ajeng Triyana Dewi; Arthur Brown; Jonny Zain (Fakultas Perikanan dan Kelautan Universitas Riau, 2022)
This study aims to analyze the catch of Sondong as the main information in managing fishing, the availability of data and information about the productivity of Sondong fishing gear fisheries in Selat Akar Village and with the management in the utilization of fish resources, the sustainability of Sondong fishing business can be maintained. The research method used in this research is a survey method used to obtain the necessary data directly from the research site. The results showed that the production of Sondong ship fluctuated. The results showed that the production of Sondong ship fluctuated. So that the annual production value of Sondong ship for 5 years also fluctuates. The productivity value of Sondong ships varies where the highest values in 2017 and 2019 show that the period was a good year in producing fishing using these fishing gear. The low productivity in 2018 was due to temporary weather anomalies, where weather conditions worsened which affected the success of the capture process. and the lowest was in 2020. And the results of the Trend of Sondong fishing gear production show that there is a high correlation that indicates that produce results in the next 3 years will increase and show that the initial production value of sondong fishing gear is relatively high.